Control Scheme for a Quadratic-Based Step-Down On-Board DC/DC Converter to Be Used in Hybrid Electric Vehicles - Carlos Arturo Antuna-Fiscal; Jesus Leyva-Ramos; Ma. Guadalupe Ortiz-Lopez; Luis Humberto Diaz-Saldierna (Energies, 2023)
This paper discusses a switching regulator with a quadratic-based step-down DC/DC converter designed using a reduced redundant power processing principle. This converter benefits from a non-complex topology, which aims to process energy more efficiently. The switching regulator can be used on-board in hybrid electric vehicles and has a non-pulsating input current, which is suitable to process energy from lithium-ion batteries. Design expressions and steady-state operating conditions are given for the converter. Models are obtained to design and implement a two-loop controller. The simplicity of this approach is of significant value in a method of design-oriented analysis, in which the analytic results can be used to make design choices. Loop-shaping techniques are used to design a robust controller to regulate the output voltage of the proposed converter under voltage variations on the lithium-ion batteries and the changes in load current requirements, as well as parameter uncertainties of the converter. The design conditions for the gains of the controller are derived. The models of the converter are verified through experimental results for a 300 W prototype and used to design a robust controller. Finally, closed-loop time and frequency domain tests are given to show the performance of the switching regulator.